Faktor Lingkungan Dalam Estimasi Biaya Infrastruktur Air Bersih: Tinjauan Terhadap Perkembangan Studi Empiris - Sri Maryati; Benny Chatib; Widiarto Widiarto; Suprihanto Notodarmodjo (Journal of Regional and City Planning, 2006)
Investment and operation of water infrastructure is expensive. In order to prevent the failure of investment and operation caused by unpredictable cost, cost estimation before the development of water infrastructure is very important. Theories and concept in water supply engineering show that environmental condition has an important role in determining cost variation of water infrastructure. This article explores to what extent environmental condition was considered in empirical cost studies. It reveals that environmental condition has not been considered comprehensively in empirical cost studies, especially cost estimation studies.Keywords: water infrastructure, cost estimation, environmental condition